Hedgehog Signaling: An Achilles’ Heel in Cancer - Madiha Niyaz; Mosin S Khan; Syed Mudassar (Translational Oncology, 2019)
Hedgehog signaling pathway originally identified in the fruit fly Drosophila is an evolutionarily conserved signaling mechanism with crucial roles in embryogenesis, growth and patterning. It exerts its biological effect through a signaling mechanism that terminates at glioma-associated oncogene (GLI) transcription factors which alternate between activator and repressor forms and mediate various responses. The important components of the pathway include the hedgehog ligands (SHH), the Patched (PTCH) receptor, Smoothened (SMO), Suppressor of Fused (SuFu) and GLI transcription factors. Activating or inactivating mutations in key genes cause uncontrolled activation of the pathway in a ligand independent manner. The ligand-dependent aberrant activation of the hedgehog pathway causing overexpression of hedgehog pathway components and its target genes occurs in autocrine as well as paracrine fashion. In adults, aberrant activation of hedgehog signaling has been linked to birth defects and multiple solid cancers. In this review, we assimilate data from recent studies to understand the mechanism of functioning of the hedgehog signaling pathway, role in cancer, its association in various solid malignancies and the current strategies being used to target this pathway for cancer treatment.